Por uma nova independência: o papel da C&T na superação do capitalismo dependente brasileiro - Santos, Wendel Ribeiro dos (2024)
The covid-19 pandemic has advanced the introduction of technological tools into the daily lives of individuals. The imperative of social isolation to curb the spread of the disease, made the virtual world gain strength and intensity in social mediation between people, which resulted in a double consequence: on the production side, large technology companies begun to play an even more vital role in the construction of socially perceived reality; while, on the consumption side, individuals experience an unprecedented level of dependence on their technological devices. Such a scenario seems quite fruitful and pertinent to question precisely the importance of the field of s&t for the advancement of human societies and, in particular, those marked by the trait of underdevelopment, which relegates them to a specific place in the global context of socioeconomic development. This thesis addresses the theme of Science and Technology, from the Brazilian dependent capitalism. To this end, we will deal with the development of s&t on national soil, through its relationship with the late capitalist system existing in the country. More than a simple tool for the advancement of technical devices that assist in the socioeconomic development of the nation, the developments in the field of s&t are quite significant of the type of place occupied by a country that is on the periphery of hegemonic capitalism, bringing to light relevant aspects of the relations engendered by nations at their most diverse levels of development. The theoretical framework will be the Marxist Theory of Dependence, as it represents one of the most relevant and original keys to a critical reading of the Brazilian reality, from the national point of view – and, therefore, beyond the theories imported from elsewhere. The final data collected points to s&t functioning more as a tool in the current liberal prescription – for the maintenance of both the dominant discourse about the path of development to be adopted by countries, as well as the socioeconomic system itself that sustains the structure of dependence and exploitation between nations – than an essential tool in the construction of a new economic reality, which would enable Brazil's independence from the countries of pioneering capitalism.